MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPLANASI MELALUI MODEL DISCOVERY LEARNING PADA SISWA DI SD - Husain, Ernawati S.; Halidu , Salma; Husain , Rusmin; Monoarfa, Fidyawati; Pulukadang, Wiwy Triyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to improve the ability to write explanatory texts in grade V students of Elementary School Laboratory, State University of Gorontalo using the Discovery Learning learning model. This type of research is Classroom Action Research (CAR), which is carried out in two cycles. The data collection techniques used are observation, testing and documentation techniques. The research process includes 4 stages: Preparation, Implementation, Monitoring and Evaluation, and Analysis and Reflection, with a total of 20 students. The results of initial observations showed that students' ability to write explanatory texts was still at a low level. Of the 20 students involved, only 5 students (25%) were able to write explanatory texts well, while 15 students (75%) were still unable. In Cycle 1 Meeting 1, the number of students who were able to write explanatory texts increased to 8 people (40%), while students who were not yet able to write explanatory texts were 12 people (60%). In Cycle 1 Meeting 2, the number of students who were able to write explanatory texts increased again to 12 people (60%), while those who were not yet able decreased to 8 people (40%). In Cycle 2 Meeting 1, the number of students who were able to write explanatory texts increased to 14 people (70%), while students who were not able to decreased to 6 people (30%). In Cycle 2 Meeting 2, the number of students who were able to write explanatory texts increased again to 18 people (90%), while those who were not able to decreased to 2 people (10%). From the results of the study, it can be concluded that the application of the Discovery Learning model can improve students' ability to write explanatory texts. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan menulis teks eksplanasi pada siswa kelas V SD Laboratorium Universitas Negeri Gorontalo dengan menggunakan model pembelajaran Discovery Learning. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK), yang dilaksanakan dalam dua siklus. Teknik pengumpulan data yang dipakai yaitu teknik observasi, tes dan dokumentasi. Proses penelitian ini mencakup 4 tahap: Persiapan, Pelaksanaan, Pemantauan dan Evaluasi, serta Analisis dan Refleksi, dengan jumlah 20 siswa. Hasil observasi awal menunjukan bahwa kemampuan menulis teks eksplanasi siswa masih berada pada tingkat rendah. Dari 20 siswa yang terlibat, hanya 5 siswa (25%) yang mampu menulis teks eksplanasi dengan baik, sedangkan 15 siswa (75%) masih belum mampu. Pada Siklus 1 Pertemuan 1, jumlah siswa yang mampu menulis teks eksplanasi meningkat menjadi 8 orang (40%), sedangkan siswa yang belum mampu menulis teks eksplanasi sebanyak 12 orang (60%). Pada Siklus 1 Pertemuan 2, jumlah siswa yang mampu menulis teks eksplanasi meningkat lagi menjadi 12 orang (60%), sementara yang belum mampu menurun menjadi 8 orang (40%). Pada Siklus 2 Pertemuan 1, jumlah siswa yang mampu menulis teks eksplanasi mengalami peningkatatan menjadi 14 orang (70%), sementara siswa yang belum mampu menurun menjadi 6 orang (30%). Pada Siklus 2 Pertemuan 2, jumlah siswa yang mampu menulis teks eksplanasi meningkat lagi menjadi 18 orang (90%), sedangkan yang belum mampu menurun menjadi 2 orang (10%). Dari hasil penelitian dapat disimpulkan bahwa penerapan model Discovery Learning dapat meningkatkan kemampuan menulis teks eksplanasi siswa.